Efektivitas Pendekatan Pembelajaran Mendalam dalam Membangun Kemampuan Menulis Teks Eksplanasi - Dewi, Anita Candra (ISOLEK: Jurnal Pendidikan, Pengajaran, Bahasa, dan Sastra, 2026)
This study aims to test the effectiveness of an immersive learning approach in improving the writing skills of explanatory texts among high school students. The method used was a quasi-experimental design with a pre-test and post-test, involving two groups: an experimental group that received instruction with an immersive approach and a control group that used conventional methods. A sample of 60 students was divided into two groups using purposive sampling. The main instrument was an explanatory text writing test, the validity and reliability of which had been tested. Data were analyzed using a t-test with a significance level of 0.05. The results showed a significant improvement in students' writing skills in the experimental group (an average increase of 16.25) compared to the control group (an average increase of 6.85), with a t-value of 3.56 (p<0.05). Observations also revealed higher student activity and motivation in the experimental group. These results indicate that the immersive learning approach is effective in improving the quality of explanatory text writing skills and can be an innovative alternative in teaching Indonesian at the high school level.